Brincar e ambientes de educação infantil: um estudo comparativo - Tathiana Martins de Carvalho (2007)
Considering the importance of the first years of life, above all its influence on latter stages of life, the present study aimed to describe the three to five year old child-plays and to compare it with the quality of their formal education. In order to do so, the Infant/Toddler Environment Rating Scale - Revised Edition (ITERS-R) and the Early Childhood Environment Rating Scale - Revised Edition (ECERS-R) were used to assess the children education quality. Besides the use of the mentioned scales, the visits of toys room of seven classrooms pertaining to seven different schools each were taped, comprising a total of 129 participants between 3 and 5 years of age. The visits lasted approximately 54 minutes. The child-play characterization developed by Tudge, Sidden e Putnam (2004) was considered in the data analysis. This system not only evaluates the main forms of child-play but also the way participants interact during child-play. A total of 554 episodes of child-play were assessed. The statistical analysis consisted of correlation analysis, variance analysis and descriptive statistics. Children played alone in 62,25% of the episodes. This may imply that children were interested in exploring new environment. In most episodes make believe child-play were not available. Among the fantastic child-play 20, 2% consisted of generalized simulations and only 6,1% simulated adult roles. Among children without fantasy Psychomotor Stimulation was the main activity, as much as for three year old children as for the five year old children. The most frequent sort of child-play for three year old was means of transportation and for five year olds was fight gun use. In this age makeup and dolls child-plays were not present. In the fantasy episodes, the makeup play was present in 65% among three year olds and in 85,71% among the 5 year olds. The fantasy play episodes followed the expected pattern in relation to gender. As dominant culture states, girls play more often with dolls and makeup and boys with fight and means of transportation. There were an increased number of episodes among five year old children. Although somewhat low, significant correlation (r=0,161 , p< .01) was established between quality of child-play and the make believe play with adult role simulation. The variance analysis indicated that schools with higher scores in the scales showed a greater number of make-believe child-play in both ages. This result points to a relation between quality of child education and the types of plays performed by the children. This activity should be stimulated in education institutions and other places.